A Blockchain-Based Decentralized, Fair and Authenticated Information Sharing Scheme in Zero Trust Internet-of-Things - Liu, Yizhi; Hao, Xiaohan; Ren, Wei; Xiong, Ruoting; Zhu, Tianqing; Choo, Kim-Kwang Raymond; Min, Geyong (IEEE transactions on computers, 2023)
Internet-of-Things (IoT) are increasingly operating in the zero-trust environments where any devices and systems may be compromised and hence untrusted. In addition, data collected by and sent from IoT devices may be shared with and processed by edge computing systems, in order to reduce the reliance on centralized (cloud) servers, leading to further security and privacy issues. To cope with these challenges, this paper proposes an innovative blockchain-enabled information sharing solution in zero-trust context to guarantee anonymity yet entity authentication, data privacy yet data trustworthiness, and participant stimulation yet fairness. This new solution is able to support filtering of fabricated information through smart contracts, effective voting, and consensus mechanisms, which can prevent unauthenticated participants from sharing garbage information. We also prove that the proposed solution is secure in the universal composability framework, and further evaluate its performance over an Ethereum-based blockchain platform to demonstrate its utility.